PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR IPA SISWA KELAS III SDN060915 JL. T.B SIMATUPANGKECAMATANMEDAN SUNGGAL TAHUN PEMBELAJARAN2018/2019 - NAIBAHO, KRISTINA PERONIKA; SILABAN, PATRI JANSON (Jurnal Ilmiah Aquinas, 2020)
This study aims to find out how the pedagogical competencies of teachers at SDN 060915 JL TB. SimatupangKecamatan Medan Sunggal and how the influence of teacher pedagogic competence on student learning outcomes in class III science subjects SDN 060915 JL. TB Simatupang Medan Sunggal District. The approach used is quantitative with the survey method. The population in this study were all students at SDN 060915 JL. TB Simatupang, Medan SunggalSubdistrict, totaling 198 students. The sample was 45 students with a sampling technique that was simple random sampling. Data collection techniques in this study used a questionnaire (questionnaire) and documentation study. The analytical technique used is the data prerequisite test, product moment correlation test and hypothesis testing using the version 21.0 of the Program For Social Science (SPSS) statistics. From the results of the research that has been found it can be concluded that the pedagogical competence of teachers in science subjects is 51.11% with sufficient categories while the learning outcomes of class III students and class IIIB are 60% with sufficient categories. Based on the analysis of the data seen from the R Squaree determination coefficient test there is an influence of the teacher's pedagogical competence on learning outcomes, the magnitude of the influence is 23.8%.